2012
DOI: 10.5007/1980-0037.2012v14n6p624
|View full text |Cite
|
Sign up to set email alerts
|

Validade e fidedignidade de um instrumento para avaliar as barreiras para o uso de bicicleta em adultos

Abstract: -The purpose of this study was to analyze the validity and reliability of an instrument to assess the perception of barriers related to bicycling for leisure and transportation in adults. The items composing the instrument were selected from the literature review on the subject. Content validity was analyzed by consulting experts in physical activity field. The reliability was assessed through internal consistency (Cronbach's alpha) and agreement (intraclass correlation coefficient (ICC), kappa coefficient and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
1
5
0
6
Order By: Relevance
“…In the agreement analysis, the Kappa index was classified from moderate (0.40-0.59) to optimal (≥0.60) 28 , similar to results found by Kienteka et al 30 (k = 0.41 to k = 0.82) and Martins & Petroski 17 , who tested an instrument to verify barriers to the practice of PA in adults (k = 0.55 to k = 0.88). In contrast, the present study presented higher concordance values compared to a study performed with a very similar population, but with another age group 16 .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In the agreement analysis, the Kappa index was classified from moderate (0.40-0.59) to optimal (≥0.60) 28 , similar to results found by Kienteka et al 30 (k = 0.41 to k = 0.82) and Martins & Petroski 17 , who tested an instrument to verify barriers to the practice of PA in adults (k = 0.55 to k = 0.88). In contrast, the present study presented higher concordance values compared to a study performed with a very similar population, but with another age group 16 .…”
Section: Discussionsupporting
confidence: 52%
“…The internal consistency analysis showed that all items significantly contributed to the construction of the questionnaire with alpha values ranging from 0.89 to 0.90. A study by Santos et al 15 aimed at developing an instrument to analyze barriers to the practice of PA in adolescents, and by Kienteka et al 30 , which analyzed the validity and reliability of an instrument to evaluate the perception of barriers to bicycle use in adults, verified similar internal consistency values (> 0.85 and> 0.72, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…No contexto brasileiro, Kienteka et al (2012) analisam a validade e fidedignidade de um instrumento para avaliar a percepção de barreiras no uso da bicicleta em adultos de uma cidade brasileira. Ao compararem ciclistas que pedalam por lazer e por transporte, os autores se colocam ao lado de outros estudos quantitativos que verificam barreiras no uso da bicicleta (Nkurunziza et al, 2012;Wooliscroft & Ganglmair-Wooliscroft, 2014).…”
Section: Percepção Do Ciclista No Uso Da Bicicletaunclassified
“…Ao compararem ciclistas que pedalam por lazer e por transporte, os autores se colocam ao lado de outros estudos quantitativos que verificam barreiras no uso da bicicleta (Nkurunziza et al, 2012;Wooliscroft & Ganglmair-Wooliscroft, 2014). Com esse instrumento, Kienteka et al (2012) identificam que as principais barreiras para o uso da bicicleta são fatores individuais, sociais e ambientais, o que reforça a compreensão socioecológica do fenômeno.…”
Section: Percepção Do Ciclista No Uso Da Bicicletaunclassified
See 1 more Smart Citation